United States Andean drug policy : background and issues for decision-makers. - PERL, Raphael F. (1992)
Examines how drug control issues are framed within the US policymaking process. Points out that US officials in the Congress and the executive branch have increasingly sought ways to measure the effectiveness of drug control policy.